HISOB-KITOB ISHLARINING TARAQQIY ETTIRILISHIDA ISLOM DINI SIVILIZATSIYASINING ROLI VA AHAMIYATI. - Xudaynazarova Dilnoza,; Utkirov Shoxzodjon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This article examines the contribution of Islamic civilization to the development of accounting and calculation systems. It highlights how Islamic economic thought, Sharia principles, and trade practices during the Islamic Golden Age influenced early bookkeeping  and  financial  recording  methods.  Islamic  scholars  emphasized  ethical values such as honesty,  justice, and transparency, which became the foundation of financial accountability. The expansion of trade and state administration required more organized  accounting  systems,  leading  to  improved  record-keeping  and  financial control. These historical developments significantly contributed to the formation of modern accounting principles and practices used today.